Community structure, diversity and biomass of trees in two forest subtypes of Pekan Forest Reserve, Pahang, Malaysia. - P., Ismail; Mohd Said, Mohd Nizam; Ibrahim, Faridah Hanum; H., Khali Aziz; I., Shamsudin; M., Samsudin; A., Latiff (Forest Research Institute Malaysia, 2009)
Two one-ha ecological plots representing Kempas-Ramin-Durian and Durian-Nyatoh forest subtypes were established in Compartment 156 and Compartment 200, respectively at Pekan Forest Reserve, Pahang to determine community structure, diversity and biomass of trees. All trees of 10 cm diameter at breast height and above were enumerated in the plots. Results showed that although tree stocking was almost similar in the two forest subtypes, the basal area, volume and total tree biomass were higher in the Kempas-Ramin-Durian subtype. Shannon-Weiner diversity index, H′ obtained in the Durian-Nyatoh subtype was however, significantly higher (p<0.05) than Kempas-Ramin Durian subtype. Morisita's Index of Dispersion (Id) showed a random distribution pattern for both forest subtypes.